Investigating the prevalence and correlates of anxiety and depression among COVID-19 patients with and without concomitant tumor conditions - Luo, Qiong; Liu, Haiyu; Zheng, Qixian; Zhang, Qianyuan; Zhang, Suyun; Weng, Guizhen; Chen, Xiangqi; Yang, Sheng (Frontiers in Psychology, 2025)
ObjectiveThis study aims to evaluate the prevalence of anxiety and depression in patients with novel coronavirus pneumonia (COVID-19), with and without tumors, and to identify associated factors for improving therapy and quality of life.MethodsSeventy-four patients diagnosed with COVID-19 were form Fujian Medical University Affiliated Union Hospital from Fujian Medical University Affiliated Union Hospital were enrolled. The Hospital Anxiety and Depression Scale, Medical Coping Modes Questionnaire, Social Support Rating Scale, Type D Personality Scale, and neutrophil-to-lymphocyte ratio (NLR) were used to compare psychological status between tumor and non-tumor groups and to analyze related factors.ResultsAmong 74 patients, those with tumors (n = 14) showed a higher prevalence of anxiety and depression than those without tumors (64.29% vs. 33.33%, p < 0.05). Social support scores and NLR differed significantly between the two groups (p < 0.05), whereas coping styles and type D personality did not (p > 0.05).ConclusionCOVID-19 patients with tumors exhibit higher rates of anxiety and depression, affected by social support and NLR. These findings emphasize the need for early multidisciplinary interventions integrating psychological and immunological assessment.